Multi-Layer Restoration to Address IP Router Outages in IP-over-EONs - Liu, Siqi; Lu, Wei; Zhu, Zuqing (2017 Asia Communications and Photonics Conference (ACP), 2017)
We discuss how to cost-effectively address the IP router outages in IP over elastic optical networks (IP-over-EONs) with multi-layer restoration (MLR), and design an auxiliary-graph (AG) based algorithm that can minimize the additional operational expenses (OPEX).